Keterlibatan dalam Ibadah: Evaluasi Manajemen Gereja terhadap Anggota Jemaat yang Beraktivitas di Luar Saat Khotbah dan Doa Syafaat - Cristina Batilmurik (PT. Penerbit Tiga Mutiara, 2025)
The phenomenon of low congregation involvement in the preaching and intercessory prayer segments indicates structural and conceptual weaknesses in church worship management, which impact the quality of the congregation’s spiritual participation. Although physical attendance is maintained, the apparent spiritual absence, reflected in passive behavior or the departure of congregants during crucial liturgical moments, reveals a management failure to holistically integrate liturgical, theological, and pastoral aspects. This study employs a descriptive qualitative approach with data collected through participatory observation and in-depth interviews to examine the role of management in designing, implementing, and evaluating worship services that facilitate meaningful spiritual engagement. The analysis confirms that weak liturgical formation, the absence of a structured participatory evaluation system, and a less dialogical pastoral approach are dominant factors contributing to low congregation participation. Worship management that is purely administrative and procedural without reinforcement of the spiritual dimension contributes to a less transformative worship atmosphere. This study recommends reforming worship management through strengthening liturgical education, innovating more participatory and contextual forms of worship, and establishing worship evaluation teams involving leadership and congregants collaboratively and sustainably. The novelty of this research lies in emphasizing worship management not merely as a technical-administrative process but as a means of dynamically and contextually shaping the congregation’s spirituality, thereby providing a conceptual contribution to developing an adaptive and transformative worship management model within the modern church environment.